3D Considerations and Outcomes of Immediate Single Implant Insertion and Provisionalization at the Maxillary Esthetic Zone A Long-Term Retrospective Follow-Up Study of Up to 18 Years - Mijiritsky Eitan (JOURNAL OF CLINICAL MEDICINE, 2021)
Aim: Long-term studies addressing the outcomes of single immediate implantation and provisionalization at the maxillary esthetic zone are needed. The current study aimed to assess such outcomes along a follow-up period of up to 18 years. Materials and methods: The current study is a continuation follow-up of our previously published up to 6-year follow-up study, dated between the years 2002-2008, performed in a private clinical practice in Tel-Aviv, Israel. A total of 15 patients (23 implants) who had been treated for single-tooth replacement at the maxillary esthetic zone since 2002, underwent clinical and radiographic follow-up evaluations. Primary outcomes included mean Marginal Bone Levels (MBL), with Bleeding on Probing (BOP), implant success rate, prosthetic and esthetic complications evaluated as secondary outcomes. Results: The implant success rate was at 100%. Bone remodeling processes were observed over the follow-up period, with 0.9 mm mean marginal bone loss observed during the first 6 years of observation, followed by -0.13 +/- 0.06 mm mean loss after 6 to 18 years. The last finding suggests bone deposition, as reported by other studies (Donati et al., 2012). At the final radiographic evaluation, a mean MBL of 1.35 mm +/- 0.16 was demonstrated. No differences with respect to implant type or site were found. A generalized absence of BOP and esthetic complications occurred in two cases as a result of continuous adjacent teeth eruption versus obvious implant ankylosis. Conclusions: Adhering to careful clinical protocols and 3D bone to implant considerations while immediately placing an anterior implant, this treatment approach offers both stable and esthetically acceptable results for the replacement of missing teeth at the maxillary esthetic zone.